Reduced Hippocampal Dentate Cell Proliferation and Impaired Spatial Memory Performance in Aged-Epileptic Rats - Cavarsan, Clarissa F.; Queiroz, Claudio M.; Santos, Jair G.; Xavier, Gilberto F.; Mello, Luiz E.; Covolan, Luciene (Frontiers in Neurology, 2013)
Increased adult neurogenesis is observed after training in hippocampal-dependent tasks and also after acutely induced status epilepticus (SE) although the specific roles of these cells are still a matter of debate. In this study, we investigated hippocampal cell proliferation and differentiation and the spatial learning performance in young or aged chronically epileptic rats. Status was induced by pilocarpine in 3 or 20-month old rats. Either two or twenty months later, rats were treated with bromodeoxyuridine (BrdU) and subsequently underwent to 8-day schedule of water maze tests. As expected, learning curves were faster in young than in aged animals (P<0.001). Chronically epileptic animals exhibited impaired learning curves compared to age-matched controls. Interestingly, the duration of epilepsy (2 or 20 months) did not correlate with the memory impairment of aged epileptic animals. The number of BrdU-positive cells was greater in young epileptic subjects than in age-matched controls. In contrast, cell proliferation was not increased in aged epileptic animals, irrespective of the time of SE induction. Finally, dentate cell proliferation was not related to performance in the water maze. Based on the present results we conclude that even though aging and epilepsy lead to impairments in spatial learning, their effects are not additive.